Case Report: Serial MR Vessel Wall Imaging Visualizes the Response of Intracranial Plaques and Assists in Decision-Making - Xiao, Jiayu; Padrick, Matthew M.; Song, Shlee S.; Fan, Zhaoyang; Schlick, Konrad H. (Frontiers in Neuroscience, 2021)
Intracranial atherosclerotic disease (ICAD) is a dynamic process that leads to ischemic stroke. Symptomatic ICAD patients still suffer a high recurrent rate even under standard treatment. In this case report, to better understand the response of intracranial atherosclerotic plaques to medication, serial MR imaging was added to standard clinical workup in a 47-year-old male patient with acute occipital lobe infarction at baseline, 3-month, 6-month and 12-month post index stroke to directly visualize the morphology and signal change of plaques. We noticed that one of the plaques showed dramatic worsening at 3-month imaging follow-up despite a decrease in low-density lipoprotein level. Early identification of patients who do not respond well to medication is critical to prevent the recurrence of cardiovascular events in ICAD patients.